2001
DOI: 10.1248/bpb.24.505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-(4-Chlorobenzyl)pyridine on Rat Hepatic Microsomal Cytochrome P450 and Drug-Metabolizing Enzymes in Vivo and in Vitro.

Abstract: The effect of 4-(4-chlorobenzyl)pyridine (4-CBP) on rat hepatic microsomal cytochrome P450 (P450) and its molecular species (CYP2B1, 2E1, 3A2, 2C11, and 2C12), and on drug-metabolizing enzyme activities were examined in vivo and in vitro. Treatment of rats with 4-CBP resulted in the induction of P450 and drug-metabolizing enzymes in a dose-dependent manner, but it was markedly inhibitory at higher dose levels. Immunoblot analyses revealed that 4-CBP induces both CYP2B1 and 2E1; however, both were decreased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…Currently, Vargas et al (1998) have reported that chemical structure requirements for the induction of Phase II enzymes in the intestine are markedly different from that for the liver. All of these findings (Lavrijsen et al, 1986;Franklin, 1987a, 1987b;Rodrigues et al, 1988;James, 1988;Laignelet et al, 1989;Papac and Franklin, 1988;Franklin, 1991Franklin, , 1992Franklin and Moody, 1992;Cho et al, 1995;Vargas et al, 1998) together with our reports (Matsuura et al, 1991;Kobayashi et al, 1992Kobayashi et al, , 1993Kobayashi et al, , 1994Kobayashi et al, , 1995Kobayashi et al, , 1996aKobayashi et al, , 1996bKobayashi et al, , 2000Kobayashi et al, , 2001Yoshida et al, 1995) of P450 enzymes by imidazole ring-containing compounds would need to have an aromatic substitutent at 1 position of the imidazole ring. Thus, investigation and elucidation of the structural feature of imidazole derivatives as P450 inducer and/or inhibitor are important for the prediction of human and animal toxicities.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Currently, Vargas et al (1998) have reported that chemical structure requirements for the induction of Phase II enzymes in the intestine are markedly different from that for the liver. All of these findings (Lavrijsen et al, 1986;Franklin, 1987a, 1987b;Rodrigues et al, 1988;James, 1988;Laignelet et al, 1989;Papac and Franklin, 1988;Franklin, 1991Franklin, , 1992Franklin and Moody, 1992;Cho et al, 1995;Vargas et al, 1998) together with our reports (Matsuura et al, 1991;Kobayashi et al, 1992Kobayashi et al, , 1993Kobayashi et al, , 1994Kobayashi et al, , 1995Kobayashi et al, , 1996aKobayashi et al, , 1996bKobayashi et al, , 2000Kobayashi et al, , 2001Yoshida et al, 1995) of P450 enzymes by imidazole ring-containing compounds would need to have an aromatic substitutent at 1 position of the imidazole ring. Thus, investigation and elucidation of the structural feature of imidazole derivatives as P450 inducer and/or inhibitor are important for the prediction of human and animal toxicities.…”
Section: Introductionsupporting
confidence: 56%
“…Many imidazole-containing compounds are able to inhibit P450-dependent drug-metabolizing enzyme activity when added in vitro to the assay medium (Lavrijsen et al, 1986;Ritter and Franklin, 1987a;Laignelet et al, 1989;Matsuura et al, 1991;Kobayashi et al, 1992Kobayashi et al, , 1995Kobayashi et al, , 2001). Benzphetamine and erythromycin N-demethylase activities are catalyzed by CYP2B1 and 3A2, respectively (Graves et al, 1987).…”
Section: Discussionmentioning
confidence: 99%